The Decorated Tenement: How Immigrant Builders and Architects Transformed the Slum in the Gilded Age - Patterson, Matt (Labour / Le Travail, 2020)
The article reviews the book, "The Decorated Tenement: How Immigrant Builders and Architects Transformed the Slum in the Gilded Age," by Zachary J. Violette.